Digital Marketing: Strategy Analysis in Micro, Small and Medium Enterprises (MSMEs) - Solehatin Ika Putri; Lina Affifatusholihah; Raisya Meina Diksastera (PT Larva Wijaya Penerbit, 2024)
The purpose of this research is to analyze the implementation of digital marketing strategies through social media carried out by MSMEs. The method in this research is descriptive-qualitative using SWOT as an analysis tool, which is carried out through the strengths, weaknesses, threats, and opportunities of MSMEs in order to determine the right strategy to be applied to MSMEs through the IE matrix. The implementation of digital marketing strategies through social media by MSMEs is not yet optimal. Social media used by MSMEs include WhatsApp, Instagram, Facebook, and TikTok. The results obtained are based on the IE matrix, namely that the position of MSMEs is in quadrant 7, which means that MSMEs are in their growth period. The right strategy for this position is to carry out concentric diversification through the addition of product lines that are related to available products, either in the form of links to similar technological aspects, use of technological facilities, or joint use of marketing networks.